Gender ideology and power relations in Sahebjam's Stoning of Soraya M: A feminist critical discourse analysis - Siboro, Meliana; Rangkuti, Rahmadsyah; Tarigan, Bahagia (LITERA, 2023)
The context of the study is the ongoing protests and demonstrations by women in many places in Iran. This study aims to examine the demonstration of gender ideology and power in Sahebjam's Stoning of Soraya M. Qualitative descriptive method is used to investigate the relationship between gender ideology and power relations and how it creates a power imbalance between men and women in Iranian society. Stoning of Soraya M by Freidoune Sahebjam, published on September 12, 1990, serves as the primary data source for this study. Data are analysed through the lens of the Critical Discourse Analysis approach, specifically Lazar's Feminist Critical Discourse Analysis (2007). The findings of the study suggest that the country's laws, including the Constitution, the Civil Code, and the Criminal Code, create a complicated legal environment for women. While the Constitution guarantees equal civil rights for men and women, religious law supersedes other laws and is frequently abused by individuals to commit crimes against women. This study reveals how gender ideology and power relations to women reflected through discourse can demonstrate how women are treated in different parts of the world. Keywords: gender ideology, power, novel, feminist